THE INFLUENCE OF SCHOOL ORIENTATION PROGRAMS (MPLS) ON STUDENTS’ ADAPTATION AND LEARNING ABILITIES IN JUNIOR HIGH SCHOOL - Siadari, Lasdamena; Herman, Herman; Rumapea, Elina Lulu Bimawati; Tumewu, Wanny Christiana; Taliupan, Ratna; Silalahi, Tiodora Fermiska (LPPM Univ. Ibn Khaldun Bogor, 2025)
The transition to junior high school is a critical period for students, often accompanied by challenges in adaptation and learning. This study investigates the influence of the Masa Pengenalan Lingkungan Sekolah (MPLS), a school orientation program, on the adaptation process and learning abilities of seventh-grade students at SMP Methodist Pematangsiantar, North Sumatera, Indonesia. Employing a descriptive qualitative design, data were collected from 144 students across six classes during the MPLS held from July 14 to 16, 2025. The study analyzed three phases of the program: preparation, implementation, and evaluation. Findings indicate that the preparation phase effectively reduced student anxiety by clarifying expectations. The implementation phase facilitated social integration, familiarization with school culture, and student engagement through interactive activities. Finally, the evaluation phase showed improvements in students’ confidence, motivation, and overall adaptation to the new environment. These results suggest that MPLS significantly supports students in navigating the challenges of school transition, positively impacting their readiness to learn and participate. The study highlights the importance of structured orientation programs in promoting emotional, social, and academic adjustment in early adolescence. Recommendations include enhancing future MPLS programs by incorporating more academic exposure and peer collaboration opportunities to further strengthen student outcomes during school transitions.